New biocomposite material from ramie fibre and natural matrix of flee secretion on albasia tree as expansion effort of teaching material - Mujiyono Mujiyono (JOURNAL OF EDUCATION, 2008)
Abstract:  A biocomposite is a composite which consists of natural fiber as reinforcement and  matrix  as  binder  agents.  Biocomposite  materials  are interesting phenomena   because  they  are  environmentally friendly,   are renewable resources, and can increase the economic level of the neighbouring people.  The objective of the present study is to look into the feasibility  of biocomposite material from secretion of albasia flea  as a binder agent and ramie fiber  as reinforcement. Secretion of albasia flea  was collected from Ciamisforest, WestJava, Indonesia with lumps type and then was reacted with methylated spiritus to liquefaction. Heating of the dilution offlea secretion at180°C in 15 minutes decreased the viscosity to become gel. The gels were layered on the surface of ramie fiber  woven roving with the hand layout method. Molding of the biocomposite was done at 180-200°C in 10 minutes after 2-4 layers of ramiefiber were soaked with gel, pressing with pressure 40MPa,  and  cooling  at room temperature in 4  hours. Density  and  tensile strengths of the biocomposite were evaluated with ASTM D638-90 standard and compared withpublicized biocomposites to know itsfeasibility. The tensile strength of the biocomposite from  60% of ramie fiber  woven roving andsecretion of albasiaflea was 80 MPa with a density of 1.17g/cm'. This result showed that the biocomposite had a relatively higher tensile strength and lower density than an epoxy or polyester  matrix. The biocomposite of the matrix of albasia flea  secretion can become a novel material, have high feasibility  based on availability of renewable resources, give simplicity of matrix processing, need no high technology on molding biocomposite, and have higher tensile strength relative to lower density. An implication of the results of the study can be in the development of new teaching material in the engineering  material  subject  of  study  in  the Faculty  of Engineering  of YogyakartaState University.Keywords: biocomposite, ramiefiber, secretion of .albasiaflea, natural matrix, tensile strength, density, binder agent, reinforcement